2019
DOI: 10.3390/ma12203359
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Understanding of the Role of Rare Earth Inclusions in the Initial Marine Corrosion Process of Microalloyed Steels

Abstract: In this study, the corrosion behavior of rare earth (RE) microalloyed steels was first evaluated through potentiodynamic polarization tests and corrosion weight loss experiments, and then the corrosion morphologies were observed by scanning electron microscope (SEM). After immersion in a NaCl solution, the sulfides (or oxygen sulfides) dissolved preferentially, followed by corrosion at the boundary between the Fe matrix and oxides. Afterwards, the inclusions fell off as a whole, which promoted pitting nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The scan rate was 0.333 mVs −1 . All electrochemical measurements were performed more than three times for greater reproducibility [ 31 , 45 ]. Electrochemical impedance spectroscopy (EIS) tests were performed at a frequency ranging from 10 5 Hz to 0.01 Hz with amplitude of 10 mV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scan rate was 0.333 mVs −1 . All electrochemical measurements were performed more than three times for greater reproducibility [ 31 , 45 ]. Electrochemical impedance spectroscopy (EIS) tests were performed at a frequency ranging from 10 5 Hz to 0.01 Hz with amplitude of 10 mV.…”
Section: Methodsmentioning
confidence: 99%
“…After adding rare earth, the lattice distortion of inclusions decreased dramatically and the dissolution of the (RE) 2 O 2 S-(RE) x S y caused pitting corrosion [ 30 ]. Using the first-principles theory, Tang et al calculated the work function of rare earth oxysulfide and confirmed that rare earth sulfide is easier to dissolve, from an atomic scale perspective, than rare earth oxide [ 31 ]. The mechanism of inclusion-induced local corrosion is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, another innovative work studied by Li and Moelans 23 provides the third explanation for the above situation when they paid attention to the effects of rareearth elements modified inclusions (Fig. 13a, c, e) on initialization of localized corrosion of pipeline steels in NaCl solution, whilst reports on modifying the corrosion resistance of steel by adding rare-earth elements have also been introduced elsewhere [94][95][96][97][98][99] . In this investigation, the bandgap values (E g ) of LaAl 2 O 3 obtained by experiment and calculation is around 5.47 eV and 5.60 eV, respectively (Fig.…”
Section: Interphase Defects-triggered Selective Dissolutionmentioning
confidence: 99%
“…Additionally, the fractions of coarse inclusions (2-3 μm) in Ti-and Cu-bearing steels were 29% and 24%, respectively, which significantly increased in comparison with the base steel (11%) ( Figure 3a). The ability of inclusions to induce localized corrosion was not only limited by the chemical composition but also influenced by the dimension and density of inclusions [25,27,33,34]. Hence, the number density and size distribution of inclusions in three types of low-alloy steels were statistically analyzed via an SEM/EDS (Figure 3a,b).…”
Section: Characterization Of Inclusionsmentioning
confidence: 99%
“…With the addition of alloying elements, such as S and Al, the number density and average size of MnS, MnO, and Al 2 O 3 obviously increased, which would lead to the decrease of corrosion resistance [ 20 , 22 , 23 ]. On the contrary, the addition of RE elements can improve the corrosion resistance of the steel, owing to the much smaller average size of the modified inclusions than that of normal inclusions [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%